Mechanisms and possibilities for the emergence of extreme floods in arid zones (Tiznit plain - Morocco) - Al-Wahidi, Farid; Abd al-Ilah, Khniba; Elmehdi, Saidi Mohamed; Abdellatif, Chhaib; Dadoun, Ali (Journal of natural sciences, life and applied sciences, 2021)
In Morocco, the dynamics of change in rainfall patterns have been underway for decades. It is characterized by increasingly frequent and violent hydrological and climatic events (floods and droughts). This work aims to study the peculiarities and mechanisms of the appearance of floods in the watershed of the Oudodou wadi (Province of Tiznit - southwestern Morocco) and conduct a frequency analysis of the extreme hydrological events associated with floods to estimate their probabilities and their return periods.In addition to the diagnosis of natural factors in the area studied and their relationship to the emergence of floods, the methodological approach adopted is divided into two stages. The first, known as historical, is based on the study of 8 flooding cases (1942 - 2014) and the delimitation of threatened areas through the representations of residents. The second step focused on analyzing the frequencies of extreme hydrological events to determine their severity and return periods. Analysis of the results showed that flood thresholds are always associated with the strength and concentration of rainfall, giving them a sudden behavior like summer floods. To guide the interventions of actors in the field, the areas threatened by flooding have been identified according to their degrees of severity. The recurrence of the flows was modeled using the GAMMA law which makes it possible to estimate the probability of occurrence of extreme events (floods) and the instantaneous flows corresponding to the return periods of 2, 5, 10, 20, 50 and 100 years. Biannual and five-year hydrological events correspond to instantaneous flows of 120 and 331 m3/s, while exceptional or even very exceptional cases have a return period of more than 50 and 100 years and correspond to instantaneous flows of 912 and 1035 m3/s.
Keywords: water basin; risk of floods; arid regions; Tiznit; Oued Odudu; Oudodou valley